Factors associated with non‐response at health‐related quality of life follow‐up in a septic shock trial. Issue 3 (27th December 2017) - Kjær, M. N.; Mortensen, C. B.; Hjortrup, P. B.; Rygård, S. L.; Andersen, I.; Perner, A.
Abstract : Background: Follow‐up of intensive care unit (ICU) patients often includes health‐related quality of life (HRQoL) surveying, but non‐responders hamper the interpretation. Our aim was to assess factors for non‐response to HRQoL survey in ICU patients with septic shock at follow‐up in a clinical trial. Methods: In a post hoc follow‐up registry study, we assessed all the Danish survivors in the Transfusion‐Requirements in Septic Shock trial patients, who were mailed the Short Form 36‐item Survey (SF‐36) 1‐year after randomization. We used covariates from the trial database merged with covariates from nation‐wide registries using the unique national identification number to explore possible factors for not responding. Five covariates were pre‐specified to be included in the primary multivariate analysis: age, number of days in hospital from randomization to follow‐up, level of education, cohabitation and employment status at follow‐up. We compared the mortality from 1‐year survival (2012–2014) till end of final follow‐up (January 2016) between non‐responders and responders. Results: We assessed 308 survivors of whom 108 (35%) were non‐responders. In the primary analysis lower age (odds ratio 1.03, 95% CI [1.01–1.05]), more admission days in hospital (1.006 [1.001–1.011]) and living alone (4.33 [2.46–7.63]) were associated with non‐responding, whereas the level of education and employment status were not. Non‐responders had a hazard ratio of 1.63 [0.97–2.72] for mortality from 1‐year follow‐up to final follow‐up as compared to the responders. Conclusion: Being younger, spending more days in hospital and living alone were all associated with non‐response at 1‐year HRQoL follow‐up among ICU patients with septic shock.